(untitled) (Research, Society and Development, 2023)
The growing concern about the disposal and recycling of solid waste is a global issue due to the environmental impacts generated as a result of incorrect disposal. The increase in the amount of waste generated per capita has increased with technological, economic and social development. Public policies that deal with the topic point out the difficulties encountered by municipalities in correctly disposing of waste, especially those related to consumption in homes. Carton packaging or Tetra Pak, developed with the aim of replacing glass packaging in the storage of milk and extending its useful life, is expanding its use within the food industry and in homes. However, a drop in the recycling of this type of packaging was observed, raising concern, as incorrect disposal contributes to an increase in solid waste generated in cities and, consequently, the environmental impact. In view of all this, there is a problem involving food packaging in the long-life category. The project aimed to promote guidance, training and awareness regarding the correct disposal and sustainable reuse of milk carton packaging among communities supported by NGOs, seeking to add technical knowledge to obtain income through the production of shelters for pets.